Analisis Hubungan antara Size, Product Life Cycle, dan Market Position dengan Penggunaan Balanced Scorecard pada Sektor Industri Manufaktur - Cindy, Cindy (Business Accounting Review, 2013)
The Increasing business competition requires companies to possess an appropriate and accurate performance measurement. Balanced scorecard is an appropriate performance measurement tool to use pertinent to the financial and non-financial aspects of the measurement. The research was conducted to know the relationships among size, product life cycle, and market position and the use of balanced scorecard in the manufacturing industry. The study was conducted to 34 manufacturing companies located in Surabaya and Sidoarjo. The manufacturing companies were business to customer types that came from the consumer goods, chemicals, and various industry sectors. The data were collected by distributing questionnaires to the managers or owners of the manufacturing companies. The data analysis technique used in this study was the Pearson correlation test to determine whether there were relationships among the size, product life cycle, and market position and the use of a balanced scorecard. The results showed that there was a positive and significant relationship among the variable size, product life cycle, and market position and the use of the balanced scorecard in the manufacturing industry sector in Surabaya and Sidoarjo. In addition, it was noted that the highest use of the balanced scorecard was on the internal business process perspective, which amounted to 26%.